Ice accretion and icing technology - Flemming, Robert J. (Society of Automotive Engineers. Electronic publications, 2015)
This title addresses, among other topics, the measurement techniques and the drop physics that apply to icing, certification for flight through ice crystal clouds and in supercooled large drops, improvements in predictive techniques, scaling methods, test facilities and techniques, and rotorcraft icing. The effects of inflight atmospheric icing can be devastating to aircraft. Universities and industry have been hard at work to respond to the challenge of maintaining flight safety in all weather conditions. ... Proposed changes in the regulations for operation in icing conditions are sure to keep this type of research and development at its highest level. This is especially true for the effects of ice crystals in the atmosphere, and for the threat associated with supercooled large drop (SLD) icing.